THE USE OF ROTATING HINGE KNEE PROSTHESIS IN REVISION TOTAL KNEE ARTHROPLASTY - Jeremic, Danilo; Jovanovic, Zelimir; Krivokapic, Branislav; Vasovic, Drasko; Zekic, Boris; Zarkovic, Nikola (Srpski medicinski časopis Lekarske komore, 2025)
Introduction: The number of total knee arthroplasty (TKA) procedures shows a growing trend in orthopedic hospitals worldwide. Although TKA has an excellent long-term survival rate, it is not surprising that, given the increased life expectancy and aging population with a more significant number of comorbidities, the frequency of revision TKA will also rise. Common indications for revision TKA represent aseptic loosening and periprosthetic fractures. Case reports: A 60-year-old female patient presented to our hospital with complaints of pain and instability of her right knee, accompanied by decreased range of motion. Primary TKA was performed in another institution nine years ago. Radiographic evaluation demonstrated aseptic loosening of TKA components, with subsidence of the tibial component into varus malposition. A 73-year-old female patient was admitted to our Hospital because of an injury to her left knee resulting from a fall from a standing height that happened five days before the presentation. Primary TKA was performed 14 years ago in our Hospital. A trauma X-ray series of the injured knee revealed a Lewis type IIB periprosthetic fracture of the tibial plateau. In both patients, revision TKA was performed using a rotating hinge implant with augmentation of the tibial defect caused by loosening in the first case and fracture in the second case. Postoperative recovery was successful in both cases, with radiographic imaging showing adequate position of the implant at 2-year follow-up. Conclusion: The use of rotating hinge knee prostheses in revision total knee arthroplasty demonstrates promising outcomes, particularly in cases involving significant bone loss and instability.